(untitled) (International Journal of Environmental Sciences, 2025)
The need of Perioplastic surgical therapy for gingival recession coverage has increased due to aesthetic awareness & need for functional comfort. The objective of this study is to compare AM & PRF membrane for surgical correction of Miller class I & II gingival recession. A randomized Controlled clinical trial for bilateral gingival recession in which 10 patients will be selected from the Department of Periodontology & Oral Implantology, Rajasthan Dental College & Hospital, Jaipur. Prior consent and ethical considerations of possible risks and benefits were informed and thoroughly prioritized. The Experimental site Group A was treated with Amniotic membrane and Experimental site Group B with Platelet rich Fibrin.